Incidence, risk factors, and outcomes of second neoplasms in patients with acute promyelocytic leukemia: the PETHEMA-PALG experience - Sobas, Marta; Knopinska-Posluszny, Wanda; Piątkowska-Jakubas, Beata; García-Álvarez, Flor; Díez, María Elena Amutio; Caballero, Mar; Martínez-Cuadrón, David; Aguiar, Eliana; González-Campos, Jose; Garrido, Ana; Algarra, Lorenzo; Salamero, Olga; et al. (Annals of hematology, 2024)
The most important challenges in acute promyelocytic leukemia (APL) is preventing early death and reducing long-term events, such as second neoplasms (s-NPLs). We performed a retrospective analysis of 2670 unselected APL patients, treated with PETHEMA "chemotherapy based" and "chemotherapy free" protocols. Only de novo APL patients who achieved complete remission (CR) and completed the three consolidation cycles were enrolled into the analysis. Out of 2670 APL patients, there were 118 (4.4%) who developed s-NPLs with the median latency period (between first CR and diagnosis of s-NPL) of 48.0 months (range 2.8-231.1): 43.3 (range: 2.8-113.9) for s-MDS/AML and 61.7 (range: 7.1-231.1) for solid tumour. The 5-year CI of all s-NPLs was of 4.43% and 10 years of 7.92%. Among s-NPLs, there were 58 cases of s-MDS/AML, 3 cases of other hematological neoplasms, 57 solid tumours and 1 non-identified neoplasm. The most frequent solid tumour was colorectal, lung and breast cancer. Overall, the 2-year OS from diagnosis of s-NPLs was 40.6%, with a median OS of 11.1 months. Multivariate analysis identified age of 35 years (hazard ratio = 0.2584; p < 0.0001) as an independent prognostic factor for s-NPLs. There were no significant differences in CI of s-NPLs at 5 years between chemotherapy-based vs chemotherapy-free regimens (hazard ratio = 1.09; p = 0.932). Larger series with longer follow-up are required to confirm the potential impact of ATO+ATRA regimens to reduce the incidence of s-NPLs after front-line therapy for APL.
Keywords: Leukemia, Promyelocytic, Acute; výsledek terapie; incidence; Retrospective Studies; akutní promyelocytární leukemie; Antineoplastic Combined Chemotherapy Protocols; Neoplasms, Second Primary; protokoly protinádorové kombinované chemoterapie; lidé; Risk Factors; retrospektivní studie; rizikové faktory; tretinoin; Pathologic Complete Response; patologická kompletní odpověď; sekundární malignity; Adult; Tretinoin; Treatment Outcome; Incidence; Humans; dospělí